PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN SUPERVISI AKADEMIK TERHADAP KINERJA GURU DENGAN MEDIASI MOTIVASI KERJA STUDI KASUS PADA GURU SD DABIN III KECAMATAN PATI KABUPATEN PATI - Rini, Kartika (Students Journal of Economic and Management, 2012)
This study aims to examine and analyze the effect of the leadership of school principals and academic supervision towards the teachersâ performance by the mediation of working motivation on Dabin III Elementary School teachers, district of Pati, Pati Regency.This research is conducted by using population method and engaging 103 teachers in Dabin III Elementary School, district of Pati, Pati Regency. The technique used in this research is filling in Region Research techniques are used to fill in a questionnaire given to the respondents. Mechanical testing data used in this study include test validity with factor analysis, the Cronbach alpha reliability test, double regression analysis, t test Determination test and assumption classic test covering Multicolonieritas, heteroscedasticity, normality test.The results of the analysis and discussion of this study show that working motivation has a role to mediateÂ  the leadership of school principal towards the teachersâ performance. The leadership of the school principals have positive and significant impact on working motivation. The academic supervision has positive and significant impact on working motivation. The leadership of the school principals have positive impact on teachersâ performance. The academic supervision has positive and significant impact on teachers performance. The working motivation has positive impact and significant on teacher performance. Suggestions which could be recommended in this research is to increase the teachersâ working motivation in learning process followed by the increasing of academic supervision jointly and enhance the role of the leadership of the school principals according to their competence. Keywords:The Leadership of School Principals, Academic Supervision, Working Motivation, and Teachersâ Performance.